Pentingnya Strategi Kepemimpinan Gereja dalam Manajemen Penginjilan dan Penarikan Jiwa - Telly Manueke; Beni Chandra Purba (PT. Penerbit Tiga Mutiara, 2024)
This paper explores the importance of church leadership strategies in evangelism management and soul-winning, focusing on the application of Biblical principles and practical strategies within the context of personal evangelism. Based on Jesus command in Matthew 28:19-20, evangelism is a primary task of the church to make all nations His disciples. Evangelism should involve all church members, not just leaders, with appropriate and effective approaches. Both general and personal evangelism methods have their respective advantages and disadvantages and should be carried out with careful planning and clear objectives. This study emphasizes the importance of patience, empathy, and prayer in the evangelism process, as exemplified by Jesus Christ and church leaders. Through the author’s personal experience of successfully baptizing family members after years of evangelism, it is evident that evangelism requires deep personal relationships, as well as consistent patience and commitment. Additionally, the involvement of the Holy Spirit is crucial for guiding and transforming human hearts, making it a key factor in successful evangelism. By implementing strategies based on personal relationships, patience, and prayer, the church can more effectively fulfill Christ’s calling and achieve sustainable spiritual growth and salvation.